Designing touch screen user interfaces for future flight deck operations - Avsar, Huseyin; Fischer, Joel E.; Rodden, Tom (2016)
Many interactional issues with Flight Management Systems (FMS) in modern flight decks have been reported. Avionics designers are seeking for ways to reduce cognitive load of pilots with the aim to reduce the potential for human error. Academic research showed that touch screen interfaces reduce cognitive effort and provide an intuitive way of interaction. A new way of interaction to manipulate radio frequencies of avionics systems is presented in this paper. A usability experiment simulating departures and approaches to airports was used to evaluate the interface and compare it with the current system (FMS). In addition, interviews with pilots were conducted to find out their personal impressions and to reveal problem areas of the interface. Analyses of task completion time and error rates showed that the touch interface is significantly faster and less prone to user input errors than the conventional input method (via physical or virtual keypad). Potential problem areas were identified and an improved interface is suggested.